PENDAMPINGAN SERTIFIKASI HALAL DAN PEMBUATAN KEFIR PADA PETERNAK KAMBING PERAH - Fitra, Deni; Mirdhayati, Irdha; Adelina, Triani; Purnamasari, Endah; Erwan, Edi; Elviriadi; Zumarni; Khairuddin; Faruq, Umar; Restu Misrianti (LPPM STAI Muhammadiyah Probolinggo, 2025)
Halal certification and diversification of goat milk products are crucial for increasing product value and improving farmers' welfare. Halal certification allows dairy products to meet Islamic standards and expand market opportunities. Currently, campus-linked goat farmers have not processed milk and remain focused on fresh milk. At Fathur Farm, halal certification assistance and kefir-making training were provided to these farmers. The methods used included counseling, socialization, and discussions, followed by an evaluation. This activity was carried out by lecturers and students from the Animal Product Technology expertise group in the Animal Science Department at Universitas Islam Negeri Sultan Syarif Kasim Riau. The program equipped farmers with skills on the halal certification process, including document preparation, uploading documents in the SIHALAL application, and obtaining the certificate. Kefir training enhanced farmers' skills, diversified and added value to their products, and supported the economic sustainability of local farmers.